2022
DOI: 10.3390/rs14236007
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Driving Factors of Drought in Growing Season in the Inner Mongolia Based on Geodetector and GWR Models

Abstract: As an important ecological security barrier in northern China, the Inner Mongolia Autonomous Region (hereinafter referred to as Inner Mongolia) is seriously affected by drought. It is of great significance to characterize the spatial distribution of drought and identify the influencing factors of drought. Due to complex interactions among drought driving factors, it is difficult to quantify the contribution of each driving factor to drought using linear correlation analysis alone. In this study, we used the St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Relevant studies have shown that in arid and semi-arid areas, vegetation growth and ecosystem health status depend directly on atmospheric precipitation [11,51]. Therefore, this study uses SPEI to test the drought monitoring ability of machine learning models.…”
Section: Drought Monitoring Proficiency Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant studies have shown that in arid and semi-arid areas, vegetation growth and ecosystem health status depend directly on atmospheric precipitation [11,51]. Therefore, this study uses SPEI to test the drought monitoring ability of machine learning models.…”
Section: Drought Monitoring Proficiency Verificationmentioning
confidence: 99%
“…Huang et al [10] showed that Inner Mongolia has a high risk of summer drought mainly due to reduced precipitation. Ji et al [11] proved that precipitation and temperature were the main factors driving the increase in drought in Inner Mongolia. Drought monitoring research is a major focus of global research [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The q statistic value ranges from [0, 1], with a higher value indicating a more pronounced spatial heterogeneity of Y [36]. If the strata are generated by the independent variable X, a larger q-value signifies a stronger explanatory power of the variable for attribute Y and, conversely, a weaker explanatory power if the q-value is smaller [57,58]. In this study, a higher q-value indicates a stronger explanatory power of the factor for the variation in SMWs.…”
Section: The Geodetector Modelmentioning
confidence: 99%
“…To evaluate seasonal meteorological drought, we specifically used SPEI-3 values for May, August, and November, denoting spring, summer, and autumn drought conditions, respectively. Given that the vegetation growing season in the IM primarily occurs from April to September, we utilized SPEI-6 value for September to characterize meteorological drought during the growing season [39].…”
Section: Meteorological Drought Indexmentioning
confidence: 99%